UPAYA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN INTERAKTIF SISWA KELAS V A SDN 013 BULUH KASAP KECAMATAN DUMAI TIMUR KOTA DUMAI - Abdullah ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low result of fifth grade students learn math A SDN 013Buluh Kasap Dumai. Of the 32 students, only 7 students who achieve specified KKM is 65. Tothe researchers conduct classroom action research with the aim to improve learningoutcomes VA SDN 013 Buluh Kasap Dumai math grade students through interactive learningmodel, the study was conducted in February 2012. The subjects were students SDN 013 BuluhKasap Dumai VA classes totaling 32 students. The data used in this research is data ofstudent learning outcomes, student activities, complete learn student and teacher activities.Instruments used in this study consisted of two research instruments are instruments learningdevice consists of a syllabus, lesson plan, student worksheets and data collection instrumentsconsist of observation of student activity sheets, teacher activity observation sheet, a testsheet. The results showed mastery of students in each cycle has increased, the base score isthe number of students who completed 7 students (21.90%), in the first cycle the number ofstudents who pass increases with the number of 16 students (50.00%), the second cycleincreases with the number of student mastery of 25 students (78.12%). It can be concludedfrom the results of fifth grade students learn math A SDN 013 Buluh Kasap Dumai can beimproved through the application of interactive learning model.